Recording The Door-To-Consultation Time for Patients Presenting to the Emergency Unit-A Clinical Audit and Re-Audit - Shahid, Maheen; Farooq, Muhammad Osama; Kamran, Javeria (Pakistan Armed Forces Medical Journal, 2025)
This Audit was focussed to assess the Door-To-Consultation time of patients who presented in emergency department, in accordance with NICE guidelines. Each audit cycle consisted of two months during which all patients presenting to the Emergency Department were assessed. Total 200 patients were assessed in each cycle. A re-audit was conducted 1 year later. Study was conducted at Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Dec 2022 to Jan 2023 and Feb to Mar 2024. In the first cycle, 129(64.5%) patients were attended within 15 minutes of arrival in the emergency department while in the second cycle, 158(79.0%) patients had a door to consultation time within 15 minutes. The repeat audit cycle demonstrated a moderate improvement in door-to-consultation times following weekly health education of ED staff on triage processes and target consultation times. Additionally, guideline posters were displayed inside and outside the ED for four weeks to reinforce these objectives.